ANALISIS YURIDIS AKTA PERJANJIAN PENGIKATAN JUAL BELI YANG OBJEKNYA MERUPAKAN HARTA BERSAMA (STUDI KASUS PUTUSAN PENGADILAN NEGERI SLEMAN NOMOR 221/PDT.G.2019/PN.SMN) - Alifia Permata Adiani (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2021)
This research aimed to determine and analyze the validity and legal consequences of a Sale and Purchase Agreement Deed whose object is common property, the notary's responsibility for the deed made before a notary and the form of legal protection for buyers who have good faith in a Sale and Purchase Agreement Deed whose object is common property. The type of research is an normative juridical research with primary and secondary data. Primary data was found by interviewing with resources person. Based on the results of the analysis, it can be concluded that the Sale and Purchase Agreement Deed based on the Sleman District Court Decision Number 221/Pdt.G/2019/Pn.Smn was valid because it had complied with the provisions in Article 1320 of the Civil Code so that the legal consequences of this agreement are that the parties are bound and causes the bound parties have legal rights and responsibility that must be carried out. The notary has civil, criminal and administrative responsibility for the Sale and Purchase Agreement Deed whose object is common property made in front of him. Keywords: Notary Deed, Sale and Purchase Agreement Deed, Common Property